Association Between Prediabetes and Retinopathy: A Meta-Analysis - Jin, Ji; Lu, Peirong (Hormone and Metabolic Research, 2021)
Diabetes confers an increased risk of microvascular complications, including retinopathy. However, whether prediabetes is also related to retinopathy has not been comprehensively examined. We performed a meta-analysis to evaluate the relationship between prediabetes and retinopathy. This meta-analysis included relevant observational studies from Medline, Embase, and Web of Science databases. A random-effect model after incorporation of the intra-study heterogeneity was selected to pool the results. Subgroup analyses were applied to evaluate the influences of study characteristics on relationship. Nine cross-sectional studies including 14 751 community dwelling adult participants were included; 3847 (26.1%) of them were prediabetic. Results showed that prediabetes was associated with a higher prevalence of retinopathy compared to normoglycemia [odds ratio (OR): 1.55, 95% confidence interval (CI): 1.10–2.20, p=0.01, I2=34%]. Sensitivity analysis by excluding one study at a time showed consistent result (OR: 1.35 to 1.73, p all<0.05). Subgroup analysis showed study characteristics such as definition of prediabetes, country of study, sample size, mean age of participants, or univariate or multivariate analyses may not significantly affect the association (p for subgroup difference all>0.05). Current evidence suggests that patients with prediabetes may be associated with higher prevalence of retinopathy as compared to those with normoglycemia. Although prospective cohort studies are needed to validate these findings, results of our meta-analysis highlighted the importance of early prevention of retinopathy in patients with prediabetes.
Keywords: retinopathy; prediabetes; prevalence; cross-sectional; meta-analysis